Utilization of Learning On Line Course in Perspective Education Management - Elfrianto, Elfrianto; Tanjung, Bahdin Nur (International Journal of Social and Management Studies, 2022)
This study aims to see how far the impact of the use of learning using learning on line courses in the learning process. It can be seen that learning objectives and motivation play an important role, because by paying attention to the motivation of students, such as the desire to expand their knowledge, become specialists, and others. Then several factors that have the use of some of the features developed are learning systems. Management system in the form of plugins and themes. The development in the form of plugins and themes is intended so that the e-learning system based on massive open online courses can be installed flexibly on various other systems if needed. You can also see Mooc user data, Based on the analysis of user profiles registered in the e-learning system based on massive open online courses, it was found that 39% of users are male, while 61% of users are female. This study uses a literature study approach from several sources that have an empirical approach.